2021
DOI: 10.1186/s12951-021-00963-9
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral administration of astatine-211-labeled gold nanoparticle for alpha therapy

Abstract: Background 211At is a high-energy α-ray emitter with a relatively short half-life and a high cytotoxicity for cancer cells. Its dispersion can be imaged using clinical scanners, and it can be produced in cyclotrons without the use of nuclear fuel material. This study investigated the biodistribution and the antitumor effect of 211At-labeled gold nanoparticles (211At-AuNP) administered intratumorally. Results AuNP with a diameter of 5, 13, 30, or 12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…In contrast, in vitro cellular uptake and DNA DSB induction of both mPEG-modi ed AuNPs were low. We also report that in vitro uptake of 211 At-labeled AuNPs does not correlate with their in vivo anticancer effects in our previous intratumoral administration study [13]. The 120 nm 211 At-AuNPs@mPEG showed evident cytotoxicity in an in vitro cellular assay, while 211 At-labeled AuNPs of smaller sizes did not show cytotoxicity.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In contrast, in vitro cellular uptake and DNA DSB induction of both mPEG-modi ed AuNPs were low. We also report that in vitro uptake of 211 At-labeled AuNPs does not correlate with their in vivo anticancer effects in our previous intratumoral administration study [13]. The 120 nm 211 At-AuNPs@mPEG showed evident cytotoxicity in an in vitro cellular assay, while 211 At-labeled AuNPs of smaller sizes did not show cytotoxicity.…”
Section: Discussionmentioning
confidence: 56%
“…We recently reported that 211 At-AuNPs@mPEG exhibited cytotoxicity when they were absorbed by the tumor cells and the intratumoral administration of 211 At-AuNPs@mPEG strongly suppressed the cancer growth in a particle size-dependent manner. Smaller particles showed a more rapid distribution in tumor regions, and 5 nm 211 At-AuNPs@mPEG showed the highest suppression of cancer growth among various sizes of AuNPs tested [13]. A similar nanoseed brachytherapy using 211 At-labeled gold nanostars has also reported signi cant inhibition of the growth of human gliomas in a murine model [25].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This approach has been utilized in several reports and has already shown effective results when labeling antibodies with 211 At 42 , 43 . An additional possible use for NPs labeled with 211 At could be brachytherapy as shown in a recent report, where tumor growth was inhibited for 38 days 44 . When administering the 211 At-PMs directly at the tumor site, accumulation in the liver can be avoided and, therefore, the degradation of the micelles and consequent deastatination may be limited.…”
Section: Resultsmentioning
confidence: 99%
“… 31 In the immunotherapy of PDAC, nanomedicines can be developed to facilitate antitumour immune responses through a series of immuno-potentiating functions after being directly injected into tumours. 32 , 33 Immunotherapy drug through intratumoural injection in PDAC exerted prominent antitumour effects and resulted in tumour decrease in several clinical trials (NCT02045589; NCT03198546). 34 , 35 Moreover, intra-tumoural delivery of agents has also been reported in the application of other tumour types.…”
Section: Discussionmentioning
confidence: 99%